Pharmacotherapy Considerations in Heart Failure with Mildly-Reduced Ejection Fraction. (February 2023) - Baker, Carrie; Perkins, Scott L.; Schoenborn, Erika; Biondi, Nicholas L.; Bowers, Riley D.
Heart failure with mildly reduced ejection fraction (HFmrEF) has been classified using various definitions since its first mention in the literature in 2014. This group was most recently defined in the Universal Definition and Classification of Heart Failure (HF) as HF with a left ventricular ejection fraction of 41% to 49%. An increasing emphasis has been placed on HFmrEF over the past several years, with many recent publications suggesting that common therapies used in HF with reduced ejection fraction provide benefit in this population as well. Patients with HFmrEF comprise approximately one-quarter of all patients with HF. The lack of authoritative guidance concerning pharmacotherapeutic approaches in these patients leaves a significant portion of HF patients without an evidence-based approach. Although it remains unclear if HFmrEF is simply a transitional state from preserved to reduced ejection fraction, or a distinct phenotype requiring medical optimization, there are clear cardiovascular benefits to managing this subset appropriately. This publication was created to help serve as a resource for clinicians on this evolving subset of HF and aid in preventing the progression of this disease state through improved therapy optimization. The objective of this article is to briefly discuss the epidemiology and pathophysiology of HFmrEF and review the pharmacology and clinical application of therapies for the management of HFmrEF.